Mind the green skills gap - GUHA, Panchali (Institutional Knowledge at Singapore Management University, 2025)
The need to build tomorrow’s sustainable green economy today. Climate change and the shift towards a net zero economy pose significant risks to jobs globally unless workers are equipped with green skills and competencies. There is already a green skills gap in the labour market that will only widen over time if it is not addressed. Comprehensive and coordinated policies must be developed to define and measure green jobs and skills, enhance educational offerings, and provide support for workers and employers during the transition.